2015
DOI: 10.1371/journal.pone.0135862
|View full text |Cite
|
Sign up to set email alerts
|

Validation and Diagnostic Efficiency of the Mini-SPIN in Spanish-Speaking Adolescents

Abstract: ObjectivesSocial Anxiety Disorder (SAD) is one of the most common mental disorders in adolescence. Many validated psychometric tools are available to diagnose individuals with SAD efficaciously. However, there is a demand for shortened self-report instruments that identify adolescents at risk of developing SAD. We validate the Mini-SPIN and its diagnostic efficiency in overcoming this problem in Spanish-speaking adolescents in Spain.MethodsThe psychometric properties of the 3-item Mini-SPIN scale for adolescen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 30 publications
1
4
1
Order By: Relevance
“…Our results are therefore in the range of comparable studies of the mini-SPIN in other languages (e.g. [ 16 , 19 , 46 ]. Thus, there is no need for a revision of the mini-SPIN including different items to enhance internal consistency, as Aderka et al (2013) have suggested [ 47 ].…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…Our results are therefore in the range of comparable studies of the mini-SPIN in other languages (e.g. [ 16 , 19 , 46 ]. Thus, there is no need for a revision of the mini-SPIN including different items to enhance internal consistency, as Aderka et al (2013) have suggested [ 47 ].…”
Section: Discussionsupporting
confidence: 79%
“…The 5-point-Likert rating scale ranges from 0=“not at all” to 4 = “extremely”. Using a cut-off score of 6 (range 0–12), the English version of the mini-SPIN has demonstrated sensitivity of 89% and specificity of 90% for detecting generalized social anxiety disorder [ 13 , 16 , 17 ]; psychometric properties of several translations in other languages have been demonstrated: Finnish [ 18 ], Spanish [ 19 ], Portuguese [ 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…Uniqueness of performance-only specifier (lower social anxiety scores and comorbidity rates) appears to be consistent with findings from other researchers (Bögels et al, 2010), who have suggested that the specifier presents a different pattern than a full spectrum of SAD. However, the prevalence of participants with a performance-only specifier in our sample (26%) among those who met SAD criteria contrasts with lower rates in adolescents (3.8%, 6.8%, and 0% in Garcia-Lopez, Sáez-Castillo, et al, 2015; Garcia-Lopez & Moore, 2015; Kerns et al, 2013, respectively) and adults (0.3%; Crome et al., 2015).…”
Section: Discussioncontrasting
confidence: 71%
“…We used the Spanish version of the Mini-SPIN, an adaptation from the Spanish SPIN scale (Garcia-Lopez et al, 2010). The Spanish version of the Mini-SPIN has been validated (Garcia-Lopez & Moore, 2015) and it has shown good psychometric properties.…”
Section: Survey Instrumentmentioning
confidence: 99%